Pulling through the Apex panel, bruised 'n battered - Abd Razak, Dzulkifli (2008)
CONCERTED attempts to persuade members of the public to believe that the Apex evaluation is a "flawed" process must be put to rest quickly. This is because the "informational" or, more seriously, "intellectual deficit" is now apparent in some of the arguments put forth. To begin with, comparing the Apex (accelerated programme for excellence) decision with another form of evaluation or assessment for purposes of a fashionable league table is like comparing apples to durians. To say that the Apex decision is flawed and, by implication, that the others are not, is in itself a flaw. There are at least three reasons.